Storage Period and Different Abiotic Factors Regulate Seed Germination of Two Apocynum Species — Cash Crops in Arid Saline Regions in the Northwestern China - Jiang, Li; She, Chaowen; Tian, Changyan; Tanveer, Mohsin; Wang, Lei (Frontiers in Plant Science, 2021)
On degraded land in arid regions, cultivation of Apocynum species can provide significant environmental benefits by preventing soil erosion and desertification. Furthermore, Apocynum venetum and A. pictum, which are mainly distributed in salt-barren lands in the northwestern region of China, are traditionally used to produce natural fiber and herbal tea. Direct sowing of both species may encounter various abiotic stresses such as drought and salinity. However, these effects on germination remain largely unknown, especially for seeds with different storage periods. The aim of this study was to evaluate the effects of storage period, light condition, temperature regime, drought and salinity on germination performances of both species. Germination experiment was carried out in November 2017. There were four replicates for each treatment and each petri dish contained 25 seeds. The results indicated that prolongation of storage period significantly decreased the germination percentage and velocity, especially under abiotic stresses. Light did not affect seed germination of A. venetum and A. pictum under any conditions. Seeds had better germination performance at 10/25 and 15/30 oC than those of seeds incubated at any other temperatures. With the increase of PEG and salinity concentrations, seed germination for both species gradually decreased, especially for seeds stored for two years. Low PEG (0-20 %) and salinity concentration (0-200 mM) did not significantly affect germination percentage of freshly matured seeds. However, long-time storage significantly decreased drought and salinity tolerance in A. venetum and A. pictum during germination stage. For saline soils in arid and semi-arid regions, freshly matured seeds or one-year-stored seeds of both Apocynum species are recommended to be sown by using drip-irrigation in spring.